Social innovation in food systems: towards food security and sustainability - Ferreiro, Maria de Fátima; Salavisa, I.; Sousa, C.; Bizarro, Sofia (16th European Conference on Innovation and Entrepreneurship, 2021)
The paper uses the concept of Social Innovation (SI) in the analysis of short supply chains in the food sector in order to understand its role in achieving food security and sustainability values. Food security and the transitions of food systems towards more sustainable models acquired a new relevance within the global scientific and political agendas since the food crisis in 2008. Short food supply chains correspond to one of the important subjects to be addressed by research in food security and sustainability. This importance relies upon the contribution of these forms of commercialization in terms of the dynamization of local economies and the contribution to environmental and ecological values considering the centrality of local products and local businesses (farms), as well as the reduction of intermediaries in the value chain. The paper considers three cases of short food supply chains in the Lisbon Metropolitan Area, addressed through a qualitative approach with the lens of the concept of Social Innovation. The results allow the identification of the dimensions of Social Innovation arising from the working of these short food supply chains, as well as key aspects of these chains such as the critical role played by producers’ networks in the supply of weekly baskets of fresh fruits and vegetables.